BIOMONITORING KUALITAS AIR SUNGAI GANDONG DENGAN BIOINDIKATOR MAKROINVERTEBRATA SEBAGAI BAHAN PETUNJUK PRAKTIKUM PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN SMP KELAS VII - Dwitawati, Diah Ari; Sulistyarsi, Ani; Widiyanto, Joko (Jurnal Florea, 2015)
Quality of the river water Gandong using bio-indicators of macroinvertebrates and utilize the results of this study to be used as the building blocks of practical guidance on the subject of environmental pollution junior class VII. The study was conducted in River Gandong Village. Ringinagung, Kab. Mabopane divided into 3 stations. Data obtained from direct observations in the field and laboratory tests. The method used is descriptive qualitative approach that gives an overview of water quality Gandong River. Data were analyzed after identifying the calculating method Family Biotic Index (FBI) based on tolerance index macroinvertebrates.The results of measurements of physical and chemical parameters, such as temperature for each station in the range of 25 Â° C-26, turbidity range 27-30 cm, the pH range 7, the current speed 0,16-0,29 m / s, DO 5,8-6 , 1 mg / L. Station II data has physical and chemical parameters lowest, but some aquatic biota able to survive despite the type and the amount is not much in the station I and III. As for the calculation of the FBI, the station I have the 6.39, 6.99 II station, and the station III 6.82. Water quality station I quite bad, but the quality of the station II and III declined to poor interpretation of the FBI. Family macroinvertebrates are most commonly found in every station is family Thiaridae and Physidae. The results of this study can be used as the building blocks of practical instructions Chapter Pollution Junior Class VII entitled "Observing types of animals macroinvertebrates in the river". Keyword : Biomonitoring, water quality, macroinvertebrates, Practical Hint